[Rezension von: Researching metaphor in the ancient near east] - Mouton, Alice (JAOS, 2024)
Researching Metaphor in the Ancient Near East. Edited by Marta Pallavidini and Ludovico Portuese. Philippika, vol. 141. Wiesbaden: Harrassowitz Verlag, 2020. Pp. xxi + 270, illus. €49 (paper).